2019
DOI: 10.3390/ani9100717
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-Rich Cells: A Novel Type of Concealed Cell in the Small Intestine of Chinese Soft-Shelled Turtles (Pelodiscus Sinensis)

Abstract: Although some studies have been conducted over the past few decades, the existence of mitochondria-rich cells (MRCs) in reptiles is still obscure. This is the first study to uncover the presence of MRCs in the small intestine of Chinese soft-shelled turtles. In this study, we investigated the ultrastructural characteristics of MRCs and the secretion of different ion transport proteins in the small intestine of Pelodiscus sinensis. Transmission electron microscopy revealed that the ultrastructural features of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…EVs from human milk were also quantified using SEM and it was observed that the size of these nanovesicles was in the range between 50 and 350 nm [ 108 ]. Transmission electron microscopy (TEM) was employed for the purpose of quantification and characterization of mitochondria-rich cells that provide cellular ions for intestinal homeostasis to study and understand its optimal regulation [ 109 ]. A cryo-transmission electron microscope was used to identify and characterize the heterogeneous populations of urinary extracellular vesicles from low centrifugation pellets [ 110 ].…”
Section: Methods Of Quantificationmentioning
confidence: 99%
“…EVs from human milk were also quantified using SEM and it was observed that the size of these nanovesicles was in the range between 50 and 350 nm [ 108 ]. Transmission electron microscopy (TEM) was employed for the purpose of quantification and characterization of mitochondria-rich cells that provide cellular ions for intestinal homeostasis to study and understand its optimal regulation [ 109 ]. A cryo-transmission electron microscope was used to identify and characterize the heterogeneous populations of urinary extracellular vesicles from low centrifugation pellets [ 110 ].…”
Section: Methods Of Quantificationmentioning
confidence: 99%
“…Before this, no one have detected the immunological role of MRCs. It was the first time, the detection of this novel immunological advance network of MRCs, although Vistro and Bai et al, observed that MRCs secreted exosomes‐MVBs pathway in the small intestine of turtle and fish (Figure 2) (Ali Vistro et al, 2019; Bai, Shi, et al, 2019). As we know the intestine is not only a site for nutritional digestion and absorption (Shi et al, 2020), but also plays an important role in immunology via the production and secretion of exosomal‐MVBs (Ayyar & Moss, 2021).…”
Section: Morphology and Functional Activities Of Mrcsmentioning
confidence: 99%
“…Mitochondrial‐rich cells (MRCs) are typical type of epithelial cells, morphologically these cells are totally different from other epithelial cells (Figure 1). These cells mainly observed in the gills, kidney, small intestine, and yolk‐sac membrane of fish (Esaki et al, 2009; Jonz & Nurse, 2006; Lin & Sung, 2003), as well as in the lower intestine of avians and reptiles (Ali Vistro et al, 2019; Elbrønd et al, 2004; Vistro, Tarique, et al, 2019). Abundant mitochondria with a high electron density and an abundance of tubular systems in the cytoplasm are morphological characteristics of these cells (Vistro, Tarique, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%